Examples in The Arts of The Quechua Language (16th-18th Centu-ries): A First Approach - Segovia Gordillo, Ana (2021)
This article explores the examples of the Quechua grammars composed between 1560 and 1753: a total of nine missionary arts. It analyses the marking of the examples, their topics, their function and their origin so that, on the one hand, it brings to light the links that exist between the grammars of this tradition and, on the other hand, it connects the examples used by the missionaries with the didactic and evangelizing purposes of these grammatical texts. To this end, this paper focuses on the analysis of the chapters related to nouns.